G-Land 3D: Augmented Reality-Based Geography Learning Media Innovation to Support Improvement of Quality Education in the Sustainable Development Goals - Fauzi, Adi Nur; Azzahmi, Zein Zidan; Pramita, Nanda Afry; Wulanningsih, Fitri; Prasastiawati, Diana (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2025)
G-Land 3D is an augmented reality-based learning media in the form of a book that displays virtual characters of geography material integrated with reality. The purpose of this study is to determine the development of learning media, the implementation of G-Land 3D at SMA N 4 Yogyakarta, and realize the SDGs points of quality education. The research method used is Research and Development (R&D) which verifies and develops G-Land 3D media with the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The types of data used are qualitative and quantitative with retrieval techniques using questionnaires, observations, and interviews. The results of the study revealed that G- Land facilitates students' understanding of geography concepts that have been known to be abstract and need to be visualized interestingly. The results of the t-test showed that there was a significant difference between students' pre-test and post-test scores, which means that there is a difference in students' understanding and ability between before and after learning geography using G-Land 3D.